Clinical and Laboratory Profile of Hospitalized Symptomatic COVID-19 Patients: Case Series Study From the First COVID-19 Center in the UAE - Hannawi, Suad; Hannawi, Haifa; Naeem, Kashif Bin; Elemam, Noha Mousaad; Hachim, Mahmood Y.; Hachim, Ibrahim. Y.; Darwish, Abdulla Salah; Al Salmi, Issa (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction COVID-19 is raising with a second wave threatening many countries. Therefore, it is important to understand COVID-19 characteristics across different countries. Methods This is a cross-sectional descriptive study of 525 hospitalized symptomatic COVID-19 patients, from the central federal hospital in Dubai-UAE during period of March to August 2020. Results UAE’s COVID-19 patients were relatively young; mean (SD) of the age 49(15) years, 130 (25%) were older than 60 and 4 (<1%) were younger than 18 years old. Majority were male(47; 78%). The mean (SD) BMI was 29 (6) kg/m2. While the source of contracting COVID-19 was not known in 369 (70%) of patients, 29 (6%) reported travel to overseas-country and 127 (24%) reported contact with another COVID-19 case/s. At least one comorbidity was present in 284 (54%) of patients and 241 (46%) had none. The most common comorbidities were diabetes (177; 34%) and hypertension (166; 32%). The mean (SD) of symptoms duration was 6 (3) days. The most common symptoms at hospitalization were fever (340; 65%), cough (296; 56%), and shortness of breath (SOB) (243; 46%). Most of the laboratory values were within normal range, but (184; 35%) of patients had lymphopenia, 43 (8%) had neutrophilia, and 116 (22%) had prolong international normalized ratio (INR), and 317 (60%) had high D-dimer. Chest x ray findings of consolidation was present in 334 (64%) of patients and CT scan ground glass appearance was present in 354 (68%). Acute cardiac injury occurred in 124 (24%), acute kidney injury in 111 (21%), liver injury in 101 (19%), ARDS in 155 (30%), acidosis in 118 (22%), and septic shock in 93 (18%). Consequently, 150 (29%) required ICU admission with 103 (20%) needed mechanical ventilation. Conclusions The study demonstrated the special profile of COVID-19 in UAE. Patients were young with diabetes and/or hypertension and associated with severe infection as shown by various clinical and laboratory data necessitating ICU admission.